Innovation strategy on the example of companies using bamboo - Piotr F. Borowski (Journal of Innovation and Entrepreneurship, 2021)
Innovations and new technologies allow companies to function, work, and develop in an ever-changing environment. The article discusses the importance of innovative strategies and presents the results of research carried out on the role of each employee group (CEO, R+D department, other workers) in implementing innovations, depending on the size of the enterprise: micro company, mini company, medium company, and large company. A look not only through the prism of the size of the organization, but also by the groups of people (knowledge group) responsible for innovation is a novelty of the research and fills the gap in research on innovation of enterprises. Moreover, as an exemplification of theory which is used in practice, the article also presents innovations related to bamboo use in many enterprises from different sectors of the economy (energy, automobile, and textile). Bamboo, thanks to its mechanical and chemical properties, can become an innovative material widely used by various companies. Innovations based on the use of bamboo become eco-innovations that support eco-efficiency and the circular economy. The cognitive and utilitarian value of completed research lies in the possibility of a broad look at the innovation strategy (including bamboo as an innovative material) and in the possibility of its implementation and application in various enterprises operating on the market.
Keywords: 650; Bamboo; Business economy; Clean energy; Eco-efficiency; Environment; Management; Mechanical processes; Strategy of innovation